If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9y = -27 Solving 2x + 9y = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. 2x + 9y + -9y = -27 + -9y Combine like terms: 9y + -9y = 0 2x + 0 = -27 + -9y 2x = -27 + -9y Divide each side by '2'. x = -13.5 + -4.5y Simplifying x = -13.5 + -4.5y
| 40x+35=515 | | 6(X+39)=252 | | 2(5-3x)=3(4x+3) | | 13(X-5)=78 | | x+(x*0.0095)=60000 | | 7(w-5)=5(w+3) | | x^2-5x-2=-8 | | 2(4-5x)=2(4x+1) | | 6(X-15)=210 | | -3/8*2/7*-3/1 | | 17+-8=9 | | 9x-5=292 | | -4(v-1)=4v-44 | | 4x+18y=21 | | 1=6x-3x | | 6x-5+4x=7x+16 | | 2=3x+10x^2 | | 3x=6-1/3y | | 2(x-3)=15-4x | | 13x^7=143 | | 4/u=-6 | | 3x-4=11+x | | 6x-4+5x=3X-7 | | x/2=4.5 | | 7+p= | | 11x=15x-40 | | .875m+.9-2m-.6= | | (m+1)*x^2-4mx+m+1=0 | | -7+4-8=24 | | 5w^2-31w=72 | | (5w-31)w=72 | | 1=6x^2-x |